Halal, Heritage, And Hi-Tech: Strengthening Inter-Civilizational Dialogue Through Muslim-Friendly Culinary Tourism In Sarawak - Andrew, Leviana; Mohd. Zamri, Norfarahzila; Mathew, Darrold Hansen; Abdul Latiff, Siti Fatimah; Yusuf, Muhammad Jastu; Borhani, Norshohanimira (Journal of Islamic, Social, Economics and Development, 2025)
Halal tourism has become a key driver of Malaysia’s tourism sector, contributing significantly to national revenue and aligning with strategic initiatives such as Visit Malaysia Year 2026. While Malaysia consistently ranks as a top destination in the Global Muslim Travel Index, Sarawak’s potential in halal tourism remains underexplored. This paper examines the intersection of halal culinary tourism, cultural heritage, and digital transformation in Sarawak, highlighting its unique gastronomic offerings and diverse cultural landscape. Using a narrative literature review, the study analyzed government policies, industry practices, and digital marketing strategies that support Muslim-friendly tourism. Findings reveal that despite strong national frameworks, Sarawak faces challenges in halal certification, digital readiness, and market positioning. The paper proposes strategic recommendations to enhance halal tourism through technology integration, stakeholder collaboration, and cultural authenticity. These insights aim to strengthen Sarawak’s competitiveness as a premier halal culinary destination and contribute to sustainable tourism development.